ASPP2 controls epithelial plasticity and inhibits metastasis through β-catenin-dependent regulation of ZEB1. - Wang, Y; Bu, F; Royer, C; Serres, S; Larkin, JR; Soto, MS; Sibson, N; Salter, V; Fritzsche, F; Turnquist, C; Koch, S; Zak, J; et al. (Nature Publishing Group, 2014)
Epithelial to mesenchymal transition (EMT), and the reverse mesenchymal to epithelial transition (MET), are known examples of epithelial plasticity that are important in kidney development and cancer metastasis. Here we identify ASPP2, a haploinsufficient tumour suppressor, p53 activator and PAR3 binding partner, as a molecular switch of MET and EMT. ASPP2 contributes to MET in mouse kidney in vivo. Mechanistically, ASPP2 induces MET through its PAR3-binding amino-terminus, independently of p53 binding. ASPP2 prevents β-catenin from transactivating ZEB1, directly by forming an ASPP2-β-catenin-E-cadherin ternary complex and indirectly by inhibiting β-catenin's N-terminal phosphorylation to stabilize the β-catenin-E-cadherin complex. ASPP2 limits the pro-invasive property of oncogenic RAS and inhibits tumour metastasis in vivo. Reduced ASPP2 expression results in EMT, and is associated with poor survival in hepatocellular carcinoma and breast cancer patients. Hence, ASPP2 is a key regulator of epithelial plasticity that connects cell polarity to the suppression of WNT signalling, EMT and tumour metastasis.